2012
DOI: 10.5187/jast.2012.54.3.209
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Egg Quality Traits in the Wholesale Market in Sri Lanka during the Storage Period

Abstract: The objective of this study was to assess the external and internal quality traits of eggs in wholesale egg market in Colombo, Sri Lanka and the effect of storage period in egg quality traits in the same market after receiving the eggs. First, a total of 482 fresh eggs were randomly collected from the above market and external egg quality traits were determined and recorded according to the definitions given in the Specification for Chicken Egg SLS 959:1992. After that, a total of 288 fresh eggs were randomly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 8 publications
5
12
0
Order By: Relevance
“…The present study showed yolk indices of 29.23, 33.35, and 39.23 for sanitized, unsanitized, and backyard eggs, respectively, on the day of collection. The results of the present study are in agreement with the results of Jayasena et al [27], wherein eggs from a wholesale market were analyzed. Yolk index values for the indigenous Kadaknath poultry breed range between 35.07 and 38.10 [26].…”
Section: Albumen Index and Yolk Indexsupporting
confidence: 93%
See 2 more Smart Citations
“…The present study showed yolk indices of 29.23, 33.35, and 39.23 for sanitized, unsanitized, and backyard eggs, respectively, on the day of collection. The results of the present study are in agreement with the results of Jayasena et al [27], wherein eggs from a wholesale market were analyzed. Yolk index values for the indigenous Kadaknath poultry breed range between 35.07 and 38.10 [26].…”
Section: Albumen Index and Yolk Indexsupporting
confidence: 93%
“…The thickness of an eggshell depends on genotype and nutritional management of hens; most importantly, dietary manganese, zinc, and selenium influence eggshell thickness [24]. Shell thickness (in mm) observed in the present study for eggs obtained from backyard poultry was in agreement with the observations of Niranjan et al [25] for Vanaraja and Parmar et al [26] for Kadaknath breeds, and also for commercial table egg samples reported by Jayasena et al [27] and Hussain et al [24].…”
Section: Shell Thicknesssupporting
confidence: 92%
See 1 more Smart Citation
“…Further, Hagan et al (2013) reported Haugh unit were significantly affected by the strain, which is in agreement with our current results. According to Jayasena et al (2012), eggs having Haugh unit value of 70 or above are considered as good quality eggs. Moreover, it was reported (Stadelman, 2002) higher Hugh unit values indicate better albumen quality.…”
Section: External Parametersmentioning
confidence: 99%
“…Further calculations were performed with the collected measurements data, to analyze the respective quality parameters. Egg shape index (ESI) was calculated by the method described by Monira et al (2003) and Jayasena et al (2012). Egg shell density (ESD) was calculated based on egg weight and dry egg shell weight according to the Riley et al (2014).…”
Section: Calculationsmentioning
confidence: 99%